Brief Report: Shortened Telomere Length in Patients With Systemic Lupus Erythematosus. Issue 5 (23rd April 2013) - Haque, Sahena; Rakieh, Chadi; Marriage, Fiona; Ho, Pauline; Gorodkin, Rachel; Teh, Lee Suan; Snowden, Neil; Day, Philip J. R.; Bruce, Ian N.
Abstract: Objective: Patients with systemic lupus erythematosus (SLE) have a higher rate of premature death compared to the general population, suggesting a phenotype of premature senescence in SLE. Telomere length can be used to assess overall biologic aging. This study was undertaken to address the hypothesis that patients with SLE have reduced telomere length. Methods: Telomere length was measured cross‐sectionally in whole blood from SLE patients and age‐matched healthy female controls, using real‐time quantitative polymerase chain reaction. SLE‐related and cardiovascular risk factors were assessed. Results: We compared telomere length in 63 SLE patients and 63 matched controls with a median age of 50.8 years (interquartile range [IQR] 37–59 years) and 49.9 years (IQR 32–60 years), respectively. The median relative telomere length in SLE patients was 0.97 (IQR 0.47–1.57), compared to 1.53 (IQR 0.82–2.29) in controls ( P = 0.0008). We then extended our cohort to measure telomere length in 164 SLE patients. Shorter telomere length was associated with Ro antibodies (β ± SE −0.36 ± 0.16; P = 0.023), and longer telomere length was associated with steroid therapy (0.29 ± 0.14; P = 0.046). We also noted an association of longer telomere length with increasing body mass index (β ± SE 0.07 ± 0.01; P < 0.0001) and tobacco smoking (0.64 ± 0.26; P = 0.016), as well as with the presence of carotid plaque (0.203 ± 0.177; P = 0.032). Conclusion: Telomere length is shortened in SLE patients compared to controls and does not appear to be a reflection of disease activity or immune cell turnover. Subsets of patients such as those positive for Ro antibodies may be particularly susceptible to premature biologic aging. The predictive value of telomere length as a biomarker of future risk of damage/mortality in SLE requires longitudinal evaluation.